Implementation of the Scholarship Program as an Effort to Improve the Quality of Junior High School (SMP) Education in Kutai Kartanegara Regency - Anggi Apdika Putra; Rahcmad Budi Suharto; Diana Lestari (International Journal of Social Sciences and Humanities, 2026)
This study examined the implementation of the Kukar Idaman Scholarship Program as an effort to improve the quality of junior high school (SMP) education in Kutai Kartanegara Regency within the framework of regional autonomy. A qualitative descriptive approach was employed, with data collected through observation, semi-structured in-depth interviews, and documentation involving scholarship recipients, parents, schools, program managers, and regional government officials. The findings showed that the program, funded through the Regional Budget (APBD), played a strategic role in reducing the economic barriers faced by students from low-income families, lowering the risk of dropping out, and increasing learning motivation and school participation at the SMP level. The driving factors were community economic needs, regional autonomy authority, and the active role of schools, while the inhibiting factors were delayed disbursement, limited socialization, and inaccurate recipient data. The study concluded that the program is an effective policy instrument for improving educational access and human resource quality, and recommended strengthening data systems, inter-agency coordination, and program sustainability.